COFFEE WASTE BIOCHAR: CHARACTERIZATION AND ZINC ADSORPTION FROM AQUEOUS SOLUTION - Sertoli, Lindiamara; Carnier, Ruan; Abreu, Cleide Aparecida de; Coscione, Aline Renée; Melo, Leônidas Carrijo Azevedo (Coffee Science - ISSN 1984-3909, 2019)
The final disposal of organic wastes has become a major challenge with increasing industrialization and population growth. Coffee wastes are examples of this, thus the conversion of these biomasses into biochar through pyrolysis could provide economic and environmental benefits, such as remediation of heavy metal polluted water. Therefore, in this work, biochar produced at 700 °C from spent coffee grounds and coffee parchment were evaluated for Zn removal from aqueous solution. Batch adsorption tests were performed with six Zn concentrations and four replicates for each material. The desorption process was performed sequentially with a pH 4.9 buffer acetic acid solution. Langmuir and Freundlich isotherms were fitted to the adsorption data using non-linear models. Batch adsorption tests showed that the adsorption was strongly dependent on biochar properties. Biochar prepared from coffee parchment was more effective at Zn binding, showing the highest adsorption capacity (0.792 mg g-1). Nevertheless, both biochars bounded Zn strongly and the adsorption process was not easily reversed.